Optimal Management of Isolated Left Vertebral Artery in Total Arch Replacement With Frozen Elephant Trunk for Aortic Dissection - Sangyu Zhou; Yanxiang Liu; Bowen Zhang; Luchen Wang; Ruojin Zhao; Mingxing Xie; Xuyang Chen; Cuntao Yu; Yaojun Dun; Xiaogang Sun (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The presence of an isolated left vertebral artery (ILVA) in patients with aortic dissection is a rare and challenging condition. This study aims to determine the optimal management of ILVA in patients with aortic dissection undergoing total arch replacement with frozen elephant trunk. Methods This retrospective study enrolled 94 patients with ILVA and aortic dissection who underwent total arch replacement with frozen elephant trunk. Patients were divided into 3 groups: 18 patients underwent ligation of ILVA, 52 underwent ILVA‐left subclavian artery transposition, and 24 underwent ILVA‐left common carotid artery transposition. Results Vertebral artery dominance was left dominant in 10.6%, symmetric in 33.0%, and right dominant in 56.4% of patients. Notably, patients who underwent ligation of ILVA had either symmetric or right‐dominant vertebral arteries, with no left‐dominant cases. No strokes were observed. Paraplegia/paraparesis (11.1% versus 11.5% versus 0%, P=0.223), mechanical ventilation time (45 [10–61] hour versus 18 [11–38] hour versus 15 [11–51] hour, P=0.855), and long‐term survival (log‐rank P=0.419) were comparable among the 3 groups. Follow‐up computed tomographic angiography confirmed patency of the left vertebral artery in all patients who underwent ILVA transposition. Conclusions Ligation of ILVA, ILVA‐left subclavian artery transposition, and ILVA‐left common carotid artery transposition are all feasible and safe strategies for managing ILVA in patients with aortic dissection undergoing total arch replacement with frozen elephant trunk.